Tumor Necrosis Factor-α Mediates the Blood-Brain Barrier Dysfunction Induced by Activated Microglia in Mouse Brain Microvascular Endothelial Cells - Tsuyoshi Nishioku; Junichi Matsumoto; Shinya Dohgu; Noriko Sumi; Kenji Miyao; Fuyuko Takata; Hideki Shuto; Atsushi Yamauchi; Yasufumi Kataoka (Elsevier, 2010)
The present study was designed to elucidate the involvement of tumor necrosis factor-α (TNF-α) release from activated microglia in the induction of blood-brain barrier (BBB) dysfunction in an in vitro co-culture system with mouse brain capillary endothelial cells (MBEC4) and microglia. Lipopolysaccharide (LPS)-activated microglia increased the permeability of MBEC4 cells to sodium-fluorescein, and this hyper-permeability was blocked by a neutralizing antibody against TNF-α. LPS stimulated microglia to facilitate TNF-α release. These findings suggested that TNF-α released from activated microglia is attributable to BBB dysfunction. Keywords:: microglia, tumor necrosis factor-α (TNF-α), blood-brain barrier